2ab*3+3xb*2-5b*4+2b*2=

Simple and best practice solution for 2ab*3+3xb*2-5b*4+2b*2= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2ab*3+3xb*2-5b*4+2b*2= equation:


Simplifying
2ab * 3 + 3xb * 2 + -5b * 4 + 2b * 2 = 0

Reorder the terms for easier multiplication:
2 * 3ab + 3xb * 2 + -5b * 4 + 2b * 2 = 0

Multiply 2 * 3
6ab + 3xb * 2 + -5b * 4 + 2b * 2 = 0

Reorder the terms for easier multiplication:
6ab + 3 * 2bx + -5b * 4 + 2b * 2 = 0

Multiply 3 * 2
6ab + 6bx + -5b * 4 + 2b * 2 = 0

Reorder the terms for easier multiplication:
6ab + 6bx + -5 * 4b + 2b * 2 = 0

Multiply -5 * 4
6ab + 6bx + -20b + 2b * 2 = 0

Reorder the terms for easier multiplication:
6ab + 6bx + -20b + 2 * 2b = 0

Multiply 2 * 2
6ab + 6bx + -20b + 4b = 0

Reorder the terms:
6ab + -20b + 4b + 6bx = 0

Combine like terms: -20b + 4b = -16b
6ab + -16b + 6bx = 0

Solving
6ab + -16b + 6bx = 0

Solving for variable 'a'.

Move all terms containing a to the left, all other terms to the right.

Add '16b' to each side of the equation.
6ab + -16b + 16b + 6bx = 0 + 16b

Combine like terms: -16b + 16b = 0
6ab + 0 + 6bx = 0 + 16b
6ab + 6bx = 0 + 16b
Remove the zero:
6ab + 6bx = 16b

Add '-6bx' to each side of the equation.
6ab + 6bx + -6bx = 16b + -6bx

Combine like terms: 6bx + -6bx = 0
6ab + 0 = 16b + -6bx
6ab = 16b + -6bx

Divide each side by '6b'.
a = 2.666666667 + -1x

Simplifying
a = 2.666666667 + -1x

See similar equations:

| csquared-5c=0 | | 5n+6n^4-7n+15n^4+13n=x | | (5x-8)(x^2+9x-10)= | | 3x^4+12x^3-36x^2=0 | | 1.4-0.2x=3.2 | | 0.07+0.4x=2 | | 5n-1=2n+8 | | 3b-9-86=11 | | -3p+2=2p+12 | | 3x^1+12x=0 | | 8lx-9l+8=32 | | 4m+7=9m-3 | | 2.4=4.2 | | 1008/48 | | 3(9-8x)+8(3x+4)=11 | | 5x-2y+20=0 | | 10-(4x-5)=6-5x | | 4w-16=12+3w | | 5w-2(w-18)=7w-15 | | (x+1)/(x-3)-3/5=4/(x-3) | | 2d^2+12d/d+6 | | 4x+5=3(x+15) | | x(3x-2)+x(4x-5)=(7x+4)(x-1) | | x+1/x-3-3/5=4/x-3 | | 3.7x-1.9=-9.3 | | 12x-8+3x-4=11x-2+3x | | 5b-20=10b+5 | | (4x^2+6x-2)+(6x^2-9x+5)= | | x^4-16x^3+60x^2=0 | | 3=-5x+1 | | 15x-14=14x | | 5/x=7/8 |

Equations solver categories